Revolutionizing U.S. Health Insurance: Leveraging Cloud Computing and Angular/React Development for Scalable, User-Centric Solutions - Venkata Raja Ravi Kumar Gelle (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative impact of integrating cloud computing with modern frontend frameworks like Angular and React in the U.S. health insurance industry. The article shows how this technological convergence is enabling insurers to develop scalable, user-centric solutions that enhance customer experiences and operational efficiency. The article discusses the benefits of cloud computing, including flexibility, security, and scalability, and how these advantages translate into improved data management and cost reduction for insurers. It then delves into the role of Angular and React in creating dynamic, responsive user interfaces that facilitate easier policy navigation, streamlined claims filing, and personalized coverage recommendations. The integration of advanced technologies such as AI and machine learning, made possible by this cloud-frontend synergy, is also explored, highlighting their potential for predictive insights and real-time data processing. The article addresses the challenges facing implementation, including data privacy concerns and legacy system migration, while also considering future trends and innovations in the industry. Ultimately, this article underscores the significant potential of these technologies to revolutionize health insurance services, improving accessibility, customer satisfaction, and overall health outcomes in the United States.